The Influence Of Work Environment And Work Discipline On Employee Performance - Enggar Tri Irawan; Syahrum Agung; Agung Wibowo (GLOBAL SCIENTS PUBLISHER, 2025)
In research with the title of the influence of the work environment and work discipline on employee performance, with the number of samples taken totalling 68 respondents of PT Sejahtera Tridaya Prima. The method used is a questionnaire research instrument distributed to employees processed using SPSS Version 26. This research was conducted at PT Sejahtera Tridaya Prima. Work Environment Variables (X1) and Work Discipline (X2) on Employee Performance (Y) are processed using correlation analysis, regression analysis, t test, f test and the coefficient of determination. The results of this study indicate that the Work Environment variable (X1) has a significant and positive effect on employee performance (Y), the work discipline variable (X2) has a significant and positive effect on employee performance (Y). Simultaneously Work Environment (X1) and Work Discipline (X2) have a significant and positive effect on employee performance (Y) of PT Sejahtera Tridaya Prima